2015
DOI: 10.11113/jt.v75.5284
|View full text |Cite
|
Sign up to set email alerts
|

Post Occupancy Evaluation of Physical Environment in Public Low-Cost Housing

Abstract: Malaysian government has introduce public low-cost housing during Malaysian Plan as an initiative to help the low-income household owners and squatters. However, in developing the low-cost housing, the quality and environmental aspects should be emphasized. Post Occupancy Evaluation (POE) is an approach in assessing existing building performance and future development of buildings to ascertain feedback from occupants after the building has been occupied for some time. This paper determines the physical environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The questionnaires were analyzed using Excel Program and the results are expected to be used as a guide for future development and indirectly to improve further design and performance of the building (Khair et al, 2015). Moreover, several human needs models were required to be accommodated in the design process (Iba, 2016) while the benchmark criteria to compare the quality of finish, services, and performance of the facilities are provided by the POE (Hassabain, 2016) in order to offer guidance for future improvements (Tookaloo & Smith, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaires were analyzed using Excel Program and the results are expected to be used as a guide for future development and indirectly to improve further design and performance of the building (Khair et al, 2015). Moreover, several human needs models were required to be accommodated in the design process (Iba, 2016) while the benchmark criteria to compare the quality of finish, services, and performance of the facilities are provided by the POE (Hassabain, 2016) in order to offer guidance for future improvements (Tookaloo & Smith, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Evaluate Occupants To evaluate occupants' comfort, satisfaction, well-being, or health [27][28][29][30][31]; investigate the factors that affect their satisfaction [32][33][34]; understand their opinions or experiences of a space [35][36][37][38]; assess their productivity [39,40]; understand occupant behavior [41][42][43][44][45]; assess occupant opinions of green building rating tools [46,47]; or evaluate the sociality of occupants [48].…”
Section: Figure 4 Number Of Projects and Number Of Buildings Per Typementioning
confidence: 99%
“…The results from factor analysis showed that the size and number of bedrooms have higher factor loading in dwelling unit features, Eigen Value (18.016). This factor included dwelling size; the size of the bedroom; living room, the size of the kitchen, a dining room, toilets and bathrooms, laundry and washing [18].…”
Section: Previous Related Studiesmentioning
confidence: 99%